1996
DOI: 10.1159/000121092
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Stenosis after Total Lumbar Laminectomy for Selective Dorsal Rhizotomy

Abstract: Knowledge of long-term outcome and complications of selective dorsal rhizotomy is limited due to the relatively recent introduction of the procedure. We describe 2 patients with cerebral palsy who developed lumbar spinal stenosis several years after selective dorsal rhizotomy. These patients also had substantial lateral trunk sway during gait and walked for several years with limited assistive devices. This abnormal gait pattern in combination with the changes from the selective dorsal rhizotomy may lead to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Spinal deformity is the most commonly reported long‐term complication, with increased risks of lumbar lordosis, scoliosis, spinal stenosis, and spondylolisthesis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spinal deformity is the most commonly reported long‐term complication, with increased risks of lumbar lordosis, scoliosis, spinal stenosis, and spondylolisthesis …”
Section: Resultsmentioning
confidence: 99%
“…The major late complication observed in this review, reported in 11% to 57% of all individuals, is spinal deformity, although most of the case series involved X-ray follow-up at a time-point clearly before skeletal maturity. 9,[25][26][27][29][30][31][32][33]38,39,48,49 The highest risk of skeletal deformity occurs during adolescent growth. Therefore, any reports of a risk of developing deformity should include a radiological evaluation at skeletal maturity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scoliosis, kyphosis or lordosis was no more prevalent in rhizotomy patients than in cerebral palsy patients in general [64]. Spinal stenosis was seen in 1.5% of patients after multilevel laminectomy or laminotomy for dorsal rhizotomy [66]. Park [67]described no spinal complications in 542 patients since 1991 after a limited laminectomy.…”
Section: Complications Of Rhizotomymentioning
confidence: 99%